THE HOCKEY COLLECTIVE IDENTITY: COGNITIVE AND PSYCHOLOGICAL APPROACHES TO THE DISCOURSE ANALYSIS (Verbal and Multimodal Aspects) - Tetiana M. Suvorova (Вісник університету ім. А. Нобеля. Серія Філологічні науки)
The associative and interpretative analysis of speech units is a traditional practice in discourse analysis that is involved in discourse studies to demonstrate how participants of communication mutually agree on the meaning they structure during the discourse. The controlled experiments are held under conditions that are relatively unusual for the natural discourse practice as in the real-time discourse the process of meaning structuring and reconstruction is due to deep involvement in the situational context. That is why the purpose of our study was to complete the experiment’s results with the mental models or situation models reflecting the categories of thinking during structuring hockey discourse in order to develop the idea of collective hockey identity that arises from the discourse because of some typical discourse structures and typical language behaviour in the process of discourse. The purpose of the research enabled several tasks to be solved. The first one was to define whether there are any peculiarities of the hockey discourse. Secondly, to reconstruct a collective hockey identity according to the discourse they construct during communication. These tasks helped us to characterize the participants of hockey discourse as the ones with the status of “in-group” members and gives them a special level of trust from other members of the social group. The methods of the discourse analysis together with the cognitive modeling compose the basis of the research. In experiments 1 and 2, we found that the “in-member” and “off-member” statuses are drawn and ascribed by the participants according to the ability to correctly structure the meaning in hockey discourse. The cognitive analysis enabled us to build a cognitive model of collective hockey identity that is based on the representations of the hockey world drawn from the discourse in social media (Instagram pages of the NHL teams). Results of the experiments and cognitive modeling of the dominant concepts of the hockey collective identity prove several hypotheses. We found social effects of status demonstration via the construction of meaning in the process of discourse and the importance of being “in-member” for effective communication and satisfaction of the participants. Differences in hockey-oriented conversation between in-group members and off-group members are proved as we assumed in the hypothesis. We provide some evidence that in-group members` and off-group members` reconstruction of the meaning in communication can differ in conversations that are focused on a specific collaborative goal, though their verbal behavior is moderated by the employment of clear general vocabulary.Though the methods of the study introduce literal and statistical noise, putting people into more naturalistic contexts and examining discourse between interlocutors who have various levels of the English language competence can reveal differences that are hidden or discouraged in the laboratory.